Implantação e atuação dos escritórios de projetos no setor público: o caso estado do Ceará - Landim, Emerson Pinheiro (2013)
The interest in project management is a topic on the rise due to the effects of globalization that has made markets more competitive, and have forced States to modernize their administration, seeking greater efficiency and effectiveness in its management because of the fiscal crisis of States. This implies a transformation of how to manage the State as concepts applied before only in the private sector are to be used as benchmarks in order to modernize and make the public service more efficient, to better meet the needs of society. This work aimed to study the implementation and performance of project offices in the State of Ceará, seeking to understand what factors led to this need, as project offices control and influence the management of the portfolio of projects, analyze the obstacles of their performance and what results the project offices have provided to the State of Ceará. The methodology characterized a case study of exploratory nature and in-depth interviews. Data collection was conducted through interviews and collection of other information that was collected during visits or from sites of the State. Ten interviews were conducted with managers Seplag who participated from the beginning of the implementation process of project management culture in the state of Ceará, which began in 2007. From the analysis of the data, it was observed that the implementation of a project management culture was performed as part of a wider administrative reform aimed to better planning of the State with the unification of their planning instruments in the secretariats and establishment of project offices that would create a methodology for project management tailored to the needs of the state to support the deployment of Public Management by Results (PMR). As for the control and influence were detected that were created, a central office that makes the role of strategic office, sectorial offices that operate tactical and project managers who perform operational management. Observed as major obstacles to the performance of the project offices, cultural challenge, lack of knowledge and experience in project management and lack of support by some managers. As a result, it was found that the implementation of project management culture in the state of Ceará has brought positive results, as both managers have a positive perception of the improvement of the results, as was also observed in the analysis of PMR some departments analyzed, that there have been positive developments in most indicators in the analyzed period 2007-2011, as a result of the implementation of administrative reform with emphasis on project management, which has allowed the achievement of goals and guidelines established in the PMR by Seplag and Government. It is concluded that more and better services have been offered to the company by the government, ensuring greater transparency and better results in the public sector.